Sexuality in the life processes context of women and men with endocrinopathies: A qualitative approach - Ledón-Llanes, Loraine (2020)
Background: endocrine disorders may affect sexuality due to hormonal changes, associated comorbidities and psychosocial impact. This topic remains poorly researched from the perspective of people with these conditions. Objectives: a qualitative research was conducted to understand the sexual experiences of women and men living with endocrine disorders that change their physical appearance. Methods: an analytical-interpretive study was carried out with a sample of 68 participants aged between 20 and 45, and treated at the National Institute of Endocrinology, Havana, Cuba. Data collection instruments were a personal information sheet, an in-depth interview guide and two projective psychological tests. Ethical aspects were considered. Results: in-depth interviews gave rise to four topics: 1) multidimensional expression of the disease, 2) the disease and life areas, 3) sexuality with the disease, and 4) coping strategies in the sexual area. These topics were linked to the meanings of health, body, gender and sexuality. Conclusions: the participants contextualized their sexual experiences within the biopsychosocial impact of the endocrine disorder, as well as the reproduction or questioning of the meanings that influenced the quality of their sexual experiences. The study showed that sexuality is a vulnerable area for the participants’ comprehensive health.